Food systems, food safety and One Health - Grace, Delia (CAB International, 2024)
This short chapter focuses on foodborne diseases, the global health burden of which rivals that of malaria or tuberculosis. Most of this burden is from the consumption of animal-source foods and fresh produce sold in the informal markets of low- and middle-income countries. The chapter considers the causes of foodborne diseases, their One Health characteristics, their health and economic burden, their trends, their associated food matrices, their associated myths and, finally, their management. Considerable progress has occurred with the management of these conditions in high-income settings; some of the lessons learned there can also be applied in low- and middle-income countries.